Spatial Analysis of Land Use and Land Cover Change Using Multi-Temporal Landsat Imagery in the Biyonga Sub-Watershed, Gorontalo - Eka Rezky Hapsari Habi; Mohammad Bisri; Linda Prasetyorini (Postgraduate, University of Mataram, 2026)
The Biyonga Sub-Watershed in Gorontalo Regency has experienced increasing land use pressure in recent years, driven by population growth and expanding socioeconomic activities. This study analyzes land use and land cover (LULC) change dynamics in the Biyonga Sub-Watershed using multi-temporal Landsat satellite imagery for 2010, 2015, 2020, and 2025. Classification was performed using the Supervised Classification method with a Maximum Likelihood approach based on a Geographic Information System (GIS), while accuracy was evaluated through a confusion matrix, Overall Accuracy (OA), and Kappa Coefficient. Results showed that forest remained the dominant land cover class throughout the observation period, accounting for the largest proportion of the watershed area across all four scenarios. A consistent decline in paddy field area was accompanied by a rise in unused land across the four years, indicating widespread land clearing. This inverse pattern suggests that agricultural land is being progressively converted into idle land rather than sustained for cultivation. The accuracy assessment confirmed the reliability of the classification results, with Overall Accuracy ranging from 84% to 88% and Kappa Coefficient ranging from 80.79% to 85.54% across the four scenario years, corresponding to good to very good accuracy categories based on the Landis and Koch (1977) standard.